CLAIMING PROPERTY FROM ILLEGAL POSSESSION OF ANOTHER PERSON (VINDICATION CLAIM) (Spectrum Journal of Innovation, Reforms and Development, 2024)
In this article, the concept of property rights and attention to property rights in our country, civil legal methods of protecting property rights, vindictive rights to protect property rights, the procedure for acquiring property from illegal possession of personal demand, as specified in the laws set norms, the application of the vindication suit in the legislation of foreign countries is described.